Scaling of Soil Moisture: A Hydrologic Perspective - Western, Andrew W.; Grayson, Rodger B.; Blöschl, Günter (Annual Review of Earth and Planetary Sciences, 2002)
▪ Abstract Soil moisture is spatially and temporally highly variable, and it influences a range of environmental processes in a nonlinear manner. This leads to scale effects that need to be understood for improved prediction of moisture dependent processes. We provide some introductory material on soil moisture, and then review results from the literature relevant to a variety of scaling techniques applicable to soil moisture. This review concentrates on spatial scaling with brief reference to results on temporal scaling. Scaling techniques are divided into behavioral techniques and process-based techniques. We discuss the statistical distribution of soil moisture, spatial correlation of soil moisture at scales from tens of meters to thousands of kilometers and related interpolation and regularization techniques, and the use of auxiliary variables such as terrain indices. Issues related to spatially distributed deterministic modeling of soil moisture are also briefly reviewed.
Keywords: land-atmosphere interaction